UK supply chain carbon mitigation strategies using alternative ports and multimodal freight transport operations. (June 2015) - Sanchez Rodrigues, V.; Pettit, S.; Harris, I.; Beresford, A.; Piecyk, M.; Yang, Z.; Ng, A.
Highlights: The cost-CO2 e tradeoffs in the port selection decision making. Minimization of overall road distance travelled. Current scenario – road maximising scenario based on the current container handling of major UK ports. Scenario (2) – shift of containers to Western and Northern ports. Scenarios (3), (4) and (5) – shift of containers to Southampton, Felixstowe and London Gateway respectively. Abstract: In the last few decades, the building evidence that CO2 e emissions lead to climate change has pointed to a need to reduce CO2 e emissions. This research uses five scenarios in the context of UK import trade to assess total CO2 e emissions and costs of import re-routing containers. The overall objective is to assess possible carbon mitigation strategies for UK supply chains by using a combination of alternative ports and revised multimodal strategies. The model adopted includes three elements: port expansion, container handling and freight transport. The alternative scenarios explore different settings modal shift and short sea shipping.